Psychotropic medication deprescribing in residential aged care facilities: An exploratory study of the knowledge and attitudes of family members of residents with dementia. (15th February 2022) - Lai, Rhoda; Withiel, Toni Dianne; Angelone, Melissa; Redpath, Cameron; O'Connor, Daniel W.; Plakiotis, Christos
Abstract: Objectives: General practitioners face many barriers to deprescribing psychotropic medications in people with dementia in nursing homes, including a lack of knowledge about their medication histories. This study explored the knowledge of family members about residents' medications and their willingness to support deprescribing. Methods: Sixty‐six family members of residents from seven residential aged care facilities participated in this cross‐sectional study. Participation involved nomination of recognised medications, rating their effectiveness and rating level of support for deprescribing. Results: Fifty‐five per cent of medications were recognised by family members; significantly fewer psychotropics were recognised than non‐psychotropic medications. Though rated as just as effective, support for deprescribing psychotropics was significantly higher. Most family members were agreeable to deprescribing with general practitioner support. Conclusions: Although there is a gap in family members' knowledge about psychotropic medications, overall they are supportive of deprescribing. Findings emphasise the need for psychoeducation among family members. Providing family members with a list of prescribed medications, specifying the type of and reason for prescription and side effects of each, is recommended to facilitate their advocacy for deprescribing on behalf of nursing home residents.